(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
After the internal audit as a tool of internal control in any organization, and helps in the evaluation of all internal control activities, as a tool to ensure compliance with the plans and policies to achieve the goals of the institution as much as possible of the efficiency, effectiveness, and should have the Internal Audit full independence and is linked to senior management, and aims to get the credibility and accuracy of information and data, and keep abreast of modern developments. The practical side includes the preparation of the questionnaire, which included a set of questions that fit the hypothesis of the research, was Tozeiha the research sample consisting of employees of the Internal Audit Department and directors of departments and the Department of Risk Management and FSA operating in the Central Bank of Iraq. The researcher reached to the set of results was the most important there is a strong positive correlation between the building checking on risks and between the cemented CBI performance, there is a discrepancy between the internal auditors in terms of full internal audit generally accepted standards of the briefing, including experience and competence and the level of due professional care and reasonable, which adversely affects the internal audit function and is reflected on the performance of the Iraqi Central Bank. The research found a number of recommendations, including: the need to expand in the rehabilitation of internal auditors capabilities, by holding risk management training courses, in order to gain experience and skills in all the different activities, and the importance of focusing on the delivery of the efficiency of internal auditors to comparable levels and bridging the gap between them from in terms of efficiency, experience and knowledge of the audit.